The role of gender inequality and health expenditure on the coverage of demand for family planning satisfied by modern contraceptives: a multilevel analysis of cross-sectional studies in 14 LAC countriesResearch in context - Laísa Rodrigues Moreira; Cauane Blumenberg; Beatriz Elena Caicedo Velasquez; Fernanda Ewerling; Alejandra Balandrán; Luis Paulo Vidaletti; Andrea Ramirez Varela; Franciele Hellwig; Rodolfo Gomez Ponce de Leon; Aluisio J.D. Barros; Mariangela Freitas Silveira; Fernando C. Wehrmeister (Elsevier, 2023)
Summary: Background: Despite international efforts to improve reproductive health indicators, little attention is paid to the contributions of contextual factors to modern contraceptive coverage, especially in the Latin America and the Caribbean (LAC) region. This study aimed to identify the association between country-level Gender Inequality and Health Expenditure with demand for family planning satisfied by modern contraceptive methods (DFPSm) in Latin American sexually active women. Methods: Our analyses included data from the most recent (post-2010) Demographic and Health Survey or Multiple Indicator Cluster Survey from 14 LAC countries. Descriptive analyses and multilevel logistic regressions were performed. Six individual-level factors were included. The effect of the country-level factors Gender Inequality Index (GII) and Current Health Expenditure on DFPSm was investigated. Findings: DFPSm ranged from 41.8% (95% CI: 40.2-43.5) in Haiti to 85.6% (95% CI: 84.9-86.3) in Colombia, with an overall median coverage of 77.8%. A direct association between the odds of DFPSm and woman's education, wealth index, and the number of children was identified. Women from countries in the highest GII tertile were less likely (OR: 0.32, 95% CI: 0.13-0.76) to have DFPSm than those living in countries in the lowest tertile. Interpretation: Understanding the contribution of country-level factors to modern contraception may allow macro-level actions focused on the population's reproductive needs. In this sense, country-level gender inequalities play an important role, as well as individual factors such as wealth and education. Funding: Bill and Melinda Gates Foundation and Associação Brasileira de Saúde Coletiva (ABRASCO).